Focal brain lesions in 16-year-old patient with epileptic seizure - different neuroimaging procedures - Paula Jankowska; Krzysztof Jankowski; Piotr Kamiński (Kazimierz Wielki University, 2019)
Introduction A brain tumor is the most common solid cancer in children and the most common cause of cancer-related death in this age group. Its first symptom presented by child may be some irritation symptoms, primarily in the form of focal seizures. In case of such problem clinician has a wide range of neuroimaging methods available. Case Report A 16-year-old girl was admitted to the Paediatric Department on December 6, 2018 after the first episode of generalized tonic-clonic seizures with retrograde amnesia. In EEG paroxysmal acute and slow theta-delta 3-4 Hz high-voltage discharge in the temporal leads and in CT with contrast no focal changes. The treatment was postponed due to fact that was the first episode of seizures in life, On June 4, 2019 a second epileptic attack occurred. CT of the head without contrast did not reveal focal changes. In EEG focal lesion in the right posterior temporo-occipital-parietal region in the form of low-voltage slow delta 1-2 Hz waves and concomitant seizure changes in the form of very numerous short discharges of acute and slow theta-delta 3-4 Hz waves. In MRI, in the occipital lobe cortex at the height of the wedge and the visual cortex after administration of the gadolinium contrast agent 3 focal lesions with contrast augmentation: 7mm and below 2 changes 15x6mm in diameter and 5mm in diameter were visualized. In the flair and T2 sequence at this height there was edema of up to 25x13mm. Conclusions CT of the head without contrast should be a screening test to exclude mainly traumatic changes and intracranial bleeding. The correct picture of such an examination does not exclude abnormalities within the brain structures. MRI is more accurate in imaging of brain structures and should be the examination of choice if CNS diagnostics is needed.